Differential Exhumation and Crustal Tilting in the Easternmost Tianshan (Xinjiang, China), Revealed by Low-Temperature Thermochronology - Gillespie, J.; Glorie, S.; Jepson, G.; Zhang, Z.; Xiao, W.; Danisik, Martin; Collins, A. (American Geophysical Union, 2017)
The easternmost Tianshan forms the eastern extremity of the modern Central Asian Orogenic Belt and represents a key locality to investigate strain propagation from the Meso-Cenozoic plate margins to the Eurasian interior. The Tianshan as a whole has been reactivated multiple times throughout the Meso-Cenozoic, but the extent of these reactivation events is yet to be fully understood. This study applies apatite fission track and apatite (U-Th-Sm)/He thermochronology to the mountain ranges of the easternmost Tianshan. Our new results suggest that the area experienced two phases of rapid cooling in the Mesozoic—during the Early to Middle Triassic and the Late Cretaceous. These cooling phases are linked to tectonic events at the distant plate margins such as the Permian to Middle Triassic closure of the Paleoasian Ocean and the Late Jurassic to Early Cretaceous Mongol Okhotsk orogeny. Fault-controlled differential exhumation and block tilting are recorded in the distribution of apatite fissio n track ages across the region. Finally, we show through a combination of multiple thermochronometers and the integration of structural analysis that the easternmost Tianshan has experienced insufficient exhumation to constrain the timing of reactivation in response to the Cenozoic collision of India with Eurasia and instead records older, Mesozoic tectonic events.